PERAN TUMBUHAN DALAM KEHIDUPAN TRADISIONAL MASYARAKAT LOKAL DI TAMAN NASIONAL GUNUNG HALIMUN JAWA BARAT - Rahayu, Mulyati; Harada, Kazuhiro (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Indigenous people who live in Gunung Halimun National Park (GHNP) rely their on their traditional life natural resources around them.The ethnobotanical research had been conducted in three villages surrounding GHNP.This research including indigenous knowledge in using plants for their daily life such as for food, medicine, fuel, ritual need etc. Most of the plants can be found wildly.Over harvesting of those wild plant might affect the sustanability the national park. Therefore, the environmental education for indigenous people is needed.